2021
DOI: 10.1016/j.atherosclerosis.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype, lifestyle and coronary artery disease: Gene-environment interaction analyses in the UK Biobank population

Abstract: Background and aims:The APOE ε4 genotype has a higher risk for developing coronary artery disease (CAD), but there is preliminary evidence that antioxidative lifestyle factors interact with APOE genotype on CAD risk. Here, we assessed the effect modification of physical activity, oily fish and polyunsaturated fatty acid (PUFA) intake with APOE genotype on risk of incident CAD. Methods: The present study comprised 345,659 white European participants from UK Biobank (mean age: 56.5 years, 45.7% men) without a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…The locus surrounding rs5117 near the APOE / APOC cluster was the most pleiotropic, associated with the variance of nine biomarkers (including lipids [TC, LDL-C, HDL-C, TG], lipoproteins [ApoA, ApoB, LipA], liver enzymes [ALT], and hsCRP). This locus has strong main effects on the same biomarkers and is known to interact with lifestyle factors in determining cardiovascular disease risk 19 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The locus surrounding rs5117 near the APOE / APOC cluster was the most pleiotropic, associated with the variance of nine biomarkers (including lipids [TC, LDL-C, HDL-C, TG], lipoproteins [ApoA, ApoB, LipA], liver enzymes [ALT], and hsCRP). This locus has strong main effects on the same biomarkers and is known to interact with lifestyle factors in determining cardiovascular disease risk 19 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These plaques can erode or rapture, while the coagulatory proteins circulating in the blood can interact with them, resulting in thrombosis and acute coronary syndrome [198,199]. Chronic CAD can cause heart failure [200], altered heart rate [201], myocardial ischemia, and left ventricular dysfunction [202]. In epidemiological research, the risk pattern for coronary artery disease has been thoroughly investigated.…”
Section: Coronary Artery Disease (Cad) and Lycopenementioning
confidence: 99%
“…2,5 ApoE gene polymorphisms affect lipoprotein clearing and lipid profile, and also the development of CAD. 6,7 Lipid metabolism is influenced by ApoE genotypes. A previous study found that ε4 carriers can increase CAD risk by approximately 42%.…”
Section: Introductionmentioning
confidence: 99%